Recent progress on the development of anisotropic gold nanoparticles: Design strategies and growth mechanism. (2nd January 2017) - Jones, Stacy; Pramanik, Avijit; Sweet, Carrie; Keyes, Anthony; Begum, Salma; Vangra, Aruna; Yu, Hongtal; Fu, Peter P.; Ray, Paresh Chandra
ABSTRACT: This review summarizes recent advances on design strategies for shape-controlled anisotropic gold nanoparticles. Detailed chemical mechanism has been discussed to understand the anisotropic growth. The effect of various chemical parameters and surface facets for the formation of different shaped anisotropic nanoparticles have been addressed.